Halatuju dan permasalahan pelaksanaan proses pra pembangunan produk baharu: Perspektif PKS Malaysia - Abu, Noor Hidayah; Md Deros, Baba; Mansor, Mohd Fitri (Penerbit UTM Press, 2015)
Small and medium-sized Enterprises (SMEs) form a substantial role in the development of Malaysian economy. In order to compete in market SMEs needs to develop, produce and introduce new product continuously.The literature reviews have found that there are relatively great numbers of SMEs fail in their new product within a year in market. The first objective of this study is to identify the main goal of SMEs implementing product pre-development process and the second objective is to identify the obstacles that can results failure in product pre-development process implementation especially among food and beverages SMEs in Malaysia.A qualitative approach were employed in this study.A total of 187 food and beverages SMEs involve in this study.The finding indicate that SMEs involve in product predevelopment process because to producing quality product, to ensure product success in market and to prepare accurate financial budget.Meanwhile, the main barrier of pre-development process implementation is lack of careful planning, lack of skill workers and inappropriate training program.The finding in this research can be a useful guideline to food and beverages SMEs for the implementation of the predevelopment process.